Middle Ear Condition at the Time of Pediatric Myringotomy Tube Placement: Pain Associations Following Intraoperative Fentanyl/Ketorolac and Seasonal Variation. (2nd November 2022) - Cohen, William G.; Zhang, Bingqing; Lee, David R.; Ampah, Steve B.; Sobol, Steven E.; Cook-Sather, Scott D.
Abstract : BACKGROUND: Ketorolac-refractory pain behavior following bilateral myringotomy and pressure equalization tube placement (BMT) is associated with the absence of middle ear fluid. Intraoperative fentanyl/ketorolac affords more reliable pain control than ketorolac alone. We hypothesized that middle ear condition would correlate with postoperative pain despite such combination therapy. We further sought to demonstrate seasonal variation in ear condition and its influence on pain. METHODS: We conducted a single-institution retrospective cohort study of healthy children (9 months–7 years), who underwent BMT by a single surgeon from 2015 to 2020. Anesthetic care included sevoflurane/nitrous oxide/oxygen/air by mask and intramuscular fentanyl/ketorolac. Left/right middle ear fluid status was recorded at the time of BMT, and ear condition (primary exposure) was dichotomized as bilateral infected (mucoid or purulent) or normal/unilateral infected. The primary outcome was maximum postanesthesia care unit Face, Legs, Activity, Cry, and Consolability (FLACC) score: 4–10 (moderate-to-severe pain) versus 0–3 (no-to-low pain). Rescue oxycodone, acetaminophen administration, and emergence agitation were secondary outcomes. Statistical analysis incorporated generalized linear mixed-effect models (GLMMs) with random intercepts to account for clustering by anesthesia provider. A year-over-year monthly time-series analysis was conducted using an autoregressive integrated moving average (ARIMA) regression model. RESULTS: Excluding recurrent cases, 1149 unique evaluable subjects remained. Bilateral infection prevalence was 39.8% (457/1149; 95% confidence interval [CI], 37.0–42.6). Probability of moderate-to-severe pain behavior was 23.5% (270/1149; 95% CI, 21.1–26.0) overall. Compared to patients with bilateral infected middle ears, those with normal/unilateral infected ears were more likely to have a FLACC score ≥4 (26.7% [185/692] versus 18.6% [85/457]; odds ratio [95% CI], 1.7 [1.2–2.3]; P = .002). Variability in pain outcome explained by the multivariable GLMM was 4.7%. Fentanyl dose response was evidenced by oxycodone administration differences ( P ≤ 0.002). Moderate-to-severe pain and emergence agitation were more likely with reduced fentanyl dosing. Bilateral infection prevalence exhibited seasonality, peaking in March and nadiring in July. However, pain outcomes did not vary by season. CONCLUSIONS: Normal/unilateral infected ears at time of pediatric BMT are associated with higher incidence of moderate-to-severe postoperative pain following intraoperative fentanyl/ketorolac administration, but the predictive value of ear condition on pain is limited. Infections were less common in the summer.